2012
DOI: 10.1016/j.eswa.2012.01.144
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent product search with soft-boundary preference relaxation

Abstract: Abstract. This paper proposes a novel method for preference relaxation in online product search, which enables consumers to make quality choices without suffering from the commonly experienced information overload. In online shopping scenarios that involve multi-attribute choice tasks, it can be difficult for consumers to process the vast amounts of information available and to make satisfactory buying decisions. In such situations consumers are likely to eliminate potentially good choices early on, using hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 63 publications
(89 reference statements)
2
11
1
Order By: Relevance
“…We show that the use of preference relaxation in product search is a valuable approach to product recommendation. Our user experiment demonstrates that classical approaches to preference relaxation (Mirzadeh & Ricci, 2007) fail to increase consumers' decision-making performance despite promising results achieved in previous work (Dabrowski et al, 2012). We show that although the results of previous studies suggest positive effects of the Standard Preference Relaxation (see Section 3) on decision performance, the strong negative effects on decision effort compromise the potential gain in decision quality.…”
Section: Motivationcontrasting
confidence: 44%
See 4 more Smart Citations
“…We show that the use of preference relaxation in product search is a valuable approach to product recommendation. Our user experiment demonstrates that classical approaches to preference relaxation (Mirzadeh & Ricci, 2007) fail to increase consumers' decision-making performance despite promising results achieved in previous work (Dabrowski et al, 2012). We show that although the results of previous studies suggest positive effects of the Standard Preference Relaxation (see Section 3) on decision performance, the strong negative effects on decision effort compromise the potential gain in decision quality.…”
Section: Motivationcontrasting
confidence: 44%
“…The user experiment described in this paper provides additional insights to the study using a set of simulations recently carried out by Dabrowski and Acton (Dabrowski et al, 2012) using the leave-one-out approach (McSherry, 2004). Dabrowski and Acton's results showed that Standard Preference Relaxation might have a positive effect on decision quality, yet it can lead to a significant increase in the average number of alternatives in result sets, which negatively impacts decision-making effort.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations